2002
DOI: 10.1146/annurev.energy.27.122001.083425
|View full text |Cite
|
Sign up to set email alerts
|

What Can History Teach Us? A Retrospective Examination of Long-Term Energy Forecasts for the United States

Abstract: ▪ Abstract  This paper explores how long-term energy forecasts are created and why they are useful. It focuses on forecasts of energy use in the United States for the year 2000 but considers only long-term predictions, i.e., those covering two or more decades. The motivation is current interest in global warming forecasts, some of which run beyond a century. The basic observation is that forecasters in the 1950–1980 period underestimated the importance of unmodeled surprises. A key example is the failure to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
153
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(154 citation statements)
references
References 30 publications
0
153
0
1
Order By: Relevance
“…The virtue of simple models is that the skill and data requirement is low and such models are more tractable rather than the hidden assumptions of complex models (Brown, 1984). This is further supported by Craig et al (2002) who found that many long-term forecasts using sophisticated models for the USA produced inaccurate forecasts in the past. Armstrong (2001) …”
Section: Simple Approachesmentioning
confidence: 92%
See 3 more Smart Citations
“…The virtue of simple models is that the skill and data requirement is low and such models are more tractable rather than the hidden assumptions of complex models (Brown, 1984). This is further supported by Craig et al (2002) who found that many long-term forecasts using sophisticated models for the USA produced inaccurate forecasts in the past. Armstrong (2001) …”
Section: Simple Approachesmentioning
confidence: 92%
“…See also Munasinghe and Meier (1993), Siddayao (1986), Codoni et al (1985), Donnelly (1987) for further details. 6 See Codoni et al (1985), Siddayao (1986), Munasinghe and Meier (1992), Craig et al (2002) for further discussions on some of these models.…”
Section: Simple Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the four scenario families, six scenario groups were developed. 14 There is no traditional trend/Business-as-Usual scenario (Craig et al 2002;Turkenburg 1993), because the long-term scope of the climate change problem requires strategic orientation on several possible developments. In SRES, there are four so-called scenario families and all scenarios are "equally possible" (SRES, p172).…”
Section: Description Of Ipcc Emissions Scenariosmentioning
confidence: 99%